(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2007)
The book Verbal Behavior (1957) was considered by B.F. Skinner as his main contribution to knowledge. Language is the most complex area of human behavior and it has been studied from many perspectives. The book Verbal Behavior was the focus of many controversies and gave origin to a large number of investigations. The first language to which the book was translated was Spanish, in 1981. At the present time the area of verbal behavior is at the center of important developments in behavior analysis, radical behaviorism and in general in scientific psychology.